Frontiers of gender equality : transnational legal perspectives - Cook, Rebecca J. (Pennsylvania studies in human rights., 2023)
Frontiers of Gender Equality is a timely and important book, especially as the world commemorates the seventy-fifth anniversary of the Universal Declaration of Human Rights in 2023. Its chapters are as imaginative and as expansive as the challenge of gender discrimination requires. While there is much to celebrate in the accomplishments to date, these authors remind us that the journeys to achieve gender equality are far from over. Significantly, the book provides maps for these journeys and suggests the kinds of research that could propel us along our way.